FORMATION OF A MODEL OF THE HUMAN CAPITAL DEVELOPMENT SYSTEM - Kudbiev Sherzod Davlyatovich (Research Parks Publishers, 2020)
The article covers the formation of a model of the human capital development system. The analysis of wages at the enterprises of the Republic of Uzbekistan, which depends on the general economic situation, is carried out. The labour market is the main source of capital accumulation and well-being in the country, and therefore, an incentive for the interest of investors and all innovative development. The main parameters of the innovative activity of enterprises and organizations in the Republic of Uzbekistan are analyzed